Measurement of residual stresses induced by sequential weld buttering and cladding operations involving a 2.25Cr-1Mo substrate material. (July 2017) - Javadi, Y.; Walsh, J.N.; Elrefaey, A.; Roy, M.J.; Francis, J.A.
Abstract: Dissimilar metal welds are necessary in high-pressure subsea systems and in cases where forged components must be welded to pipelines. F22 (2.25Cr-1Mo) steel is often used in such forged steel components and, since this steel cannot enter service without undergoing post-weld heat treatment (PWHT), the components are usually prepared for field welds through the application of a buttering layer. Furthermore, a weld overlay is deposited for the purpose of mitigating corrosion. This combination of multiple welding tasks and dissimilar materials leads to the possibility of developing substantial residual stresses. This study aims to provide insights to the evolution of residual stresses at each stage of the welding operation. The assessment has been undertaken on laboratory-scale weld mock-ups using the contour method for residual stress measurement, and incremental centre hole drilling. It was found that both buttering and cladding introduce near-yield levels of tensile residual stresses, but that these stresses are successfully relieved upon PWHT. Graphical abstract: Highlights: Dissimilar metal welding of deepwater subsea installations was studied. Weld mock-ups were manufactured by buttering, cladding and PWHT processes. The evolution of residual stresses at each stage of manufacturing was studied. Contour method was applied for the purpose of generating 2D residual stress maps. Buttering and cladding introduced high levels of tensile residual stresses.